APPROACHES TO THE DEVELOPMENT OF BIOANALYTICAL METHODS FOR DETERMINATION OF UNSTABLE SUBSTANCES IN BIOLOGICAL FLUIDS - A. L. Khokhlov; I. I. Yaichkov; Yu. A. Dzhurko; M. Ryska; V. Kubeš; L. N. Shitov (Acta Biomedica Scientifica, 2018)
The approaches to bioanalytical method development for determination of substances which contain unstable functional groups in the structure are described. The oxidation and the hydrolysis are main causes of the decomposition of substances in biological fluids. Phenolic hydroxyls contain drugs were selected as examples of oxidable compounds, glucuronides of drugs were selected as examples of hydrolysable compounds. Determination of mycophenolic acid, which contains one phenolic hydroxyl and metabolized by formation of glucuronides, in plasma was performed using high performance liquid chromatography with mass-spectrometry and tandem mass-spectrometry detection. Methyldopa, which contains two phenolic hydroxyls, in stabilized plasma was assayed by high performance liquid chromatography – tandem mass-spectrometry in the range of 0.02–3.00 μg/ml. Concentrations of desmethyl mebeverine acid, which contains in the structure one phenolic hydroxyl and metabolized by formation of phenolic glucuronide, was measured simultaneously with mebeverine acid in the range of 10–2000 ng/ml. The influence of the ion source conversion of glucuronides on the quantitative determination of the substances was studied in the initial part of methods development. The next, selection of anticoagulants based on the study of short-term stability and freeze/thaw stability of the analytes and back conversion of their glucuronides was performed. The combination of anticoagulant K3EDTA and the antioxidant solution containing a mixture of ascorbic acid, sodium sulfite and sodium hydrogen carbonate in the concentrations of 5.0 %, 0.2 % and 2.4 %, respectively, was used to prevent degradation of methyldopa.